INTENSI UNTUK BERBAGI PENGETAHUAN SAAT PEMBUATAN SOP PADA KARYAWAN DIVISI FINANCE DAN SALES PT X - Yosef Arya Wicaksana; B. P. Dwi Riyanti (MANASA, 2015)
Knowledge sharing is one of the important stages in organization’s knowledge management. Standard Operating Procedure (SOP) construction is one example of organization’s knowledge sharing activity. SOP would be well constructed by participatively involve employees because they know best about each activity in their job. To picture knowledge sharing activity in SOP construction, this research used Theory of Planned Behavior as a theoretical framework. The aim of this research was to look at employee’s knowledge sharing intention in SOP construction and factors which shaped their intention, such as attitude, subjective norms, and perceived behavioral control (PBC).This research used qualitative approach. Interviews were conducted to five respondents from the two divisions of the organization. The interviews guideline was adapted from elicitation beliefs’ questions constructed by Ajzen. The result showed that most respondents showed intention to share knowledge in SOP construction, while PBC was being evaluated as the most instrumental factor in shaping that intention. Limited intention is the result of the absence of some factors regarding knowledge sharing facility such as time availability, discussion forum and formal guideline about knowledge sharing activity. Target of the intervention which constructed by taking a closer look into that factors.